Influences of GABAergic Inhibition in the Dorsal Medulla on Contralateral Swallowing Neurons in Rats. (4th November 2020) - Kinoshita, Shota; Sugiyama, Yoichiro; Hashimoto, Keiko; Fuse, Shinya; Mukudai, Shigeyuki; Umezaki, Toshiro; Dutschmann, Mathias; Hirano, Shigeru
Abstract : Objectives: We aimed to examine the effect of unilateral inhibition of the medullary dorsal swallowing networks on the activities of swallowing‐related cranial motor nerves and swallowing interneurons. Methods: In 25 juvenile rats, we recorded bilateral vagal nerve activity (VNA) as well as unilateral phrenic and hypoglossal activity (HNA) during fictive swallowing elicited by electrical stimulation of the superior laryngeal nerve during control and following microinjection of the GABA agonist muscimol into the caudal dorsal medulla oblongata in a perfused brainstem preparation. In 20 animals, swallowing interneurons contralateral to the muscimol injection side were simultaneously recorded extracellularly and their firing rates were analyzed during swallowing. Results: Integrated VNA and HNA to the injection side decreased to 49.0 ± 16.6% and 32.3 ± 17.9%, respectively. However, the VNA on the uninjected side showed little change after muscimol injection. Following local inhibition, 11 out of 20 contralateral swallowing interneurons showed either increased or decreased of their respective firing discharge during evoked‐swallowing, while no significant changes in activity were observed in the remaining nine neurons. Conclusion: The neuronal networks underlying the swallowing pattern generation in the dorsal medulla mediate the ipsilateral motor outputs and modulate the contralateral activity of swallowing interneurons, suggesting that the bilateral coordination of the swallowing central pattern generator regulates the spatiotemporal organization of pharyngeal swallowing movements. Level of Evidence: NA Laryngoscope, 131:2187–2198, 2021